PERSEPSI SISWA TENTANG MATERI PERSAMAAN DASAR AKUNTANSI KELAS XI IPS SMA ISLAM BAWARI PONTIANAK - Juliyanti, Dwi Retno; Matsum, Junaidi H; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study is entitled â€œStudentsâ€™ perceptions towards accounting basic equations of XI-class students of social science in Bawari IslamicSenior High School Pontianakâ€.Â The general statement of the problem stood on studentsâ€™ perceptions about the subject of accounting equation which was divided into three specific questions. Those questions were as follows: How is studentâ€™s perception about the definition of accounting equation? How is studentâ€™s perception about implementation of using formula to calculate accounting equation? How is studentâ€™s perception about constructing financial statement material? For the method of investigation, the writer used descriptive method with qualitative approach. Direct communication such as interview and documentation acted as the techniques for data collection.Â The research instruments were interview guide and documentation study. The result of the study showed that (1) studentsâ€™ perceptions about the definition of accounting equation were more or less similar sinceÂ in understanding theÂ structure of financial statement materials was categorized as easy to be understood. It was proved by studentsâ€™ abilities in defining accounting equation correctly (2) Studentsâ€™ perceptions about implementation of using formula to calculate accounting equation could be categorized in the medium level. However, the interviewees (students) stated that â€˜it is difficult to analyze the transaction and to locate the account at the correct placeâ€™ (3) Studentsâ€™ perception about constructing financial statement material based on accounting equation was categorized as hard due to the interview result and their scores were unsustainable. From the scores of their daily works, only 2 out of 6 reached KKM.Â Keywords: Studentsâ€™ perceptions, accounting equation material